2008
DOI: 10.1177/1352458507082724
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the `Multiple Sclerosis Quality of Life Instrument' in Hungarian

Abstract: Health-related quality of life measurements are gaining more importance in the study and clinical practice of multiple sclerosis. The aim of our study was the adaptation of the Multiple Sclerosis Quality of Life Instrument (MSQOL-54) in Hungarian. The study was carried out at the Department of Neurology, University of Szeged and two other multiple sclerosis centers. The Hungarian translation of the questionnaire was given to patients at the outpatient units of the neurology departments. The EDSS score of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
(25 reference statements)
3
17
0
2
Order By: Relevance
“…This can also be observed in other studies on translations of the MSQoL-54 [10][11][12][13][14], including the original [4]. Among these, some also observed that the highest percentage of items with no response on sexual function and satisfaction with sexual function come from female patients [10,12,14]. This differs from our results where the proportion was 1:1, but in a smaller sample than that of the validation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This can also be observed in other studies on translations of the MSQoL-54 [10][11][12][13][14], including the original [4]. Among these, some also observed that the highest percentage of items with no response on sexual function and satisfaction with sexual function come from female patients [10,12,14]. This differs from our results where the proportion was 1:1, but in a smaller sample than that of the validation.…”
Section: Discussionsupporting
confidence: 74%
“…This was not an interpretation, embarrassment, or misunderstanding problem, but rather because they had not had sexual intercourse in the last four weeks. This can also be observed in other studies on translations of the MSQoL-54 [10][11][12][13][14], including the original [4]. Among these, some also observed that the highest percentage of items with no response on sexual function and satisfaction with sexual function come from female patients [10,12,14].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Patient-reported outcome (PRO) studies, including HRQoL studies, have not appeared in Hungary until the recent years and were mainly carried out in adult populations [12][13][14][15][16][17][18][19][20]. As the standards of care and results of medical care of children with heart disease in Hungary correspond to international recommendations, we considered it important to assess the outcomes of Hungarian pediatric cardiology care from the patients' point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Description of MS-specific instruments used in the assessment of health-related quality of life (1) Comparing several selected studies evaluating the quality of life in patients with MS (MSQOL); the differences in overall quality of life were found to be minimal. The overall quality of life in patients was evaluated as 50.50 (5), 59.39 (8), 58.20 (13) (Table 3).…”
Section: Original Articlesmentioning
confidence: 99%